A Single Case of Rosai–Dorfman Disease Marked by Pathologic Fractures, Kidney Failure, and Liver Cirrhosis Treated with Single-Agent Cladribine - Sasaki, Koji; Pemmaraju, Naveen; Westin, Jason R.; Wang, Wei-Lien; Khoury, Joseph D.; Podoloff, Donald A.; Moon, Bryan; Daver, Naval; Borthakur, Gautam (Frontiers in Oncology, 2014)
Rosai-Dorfman disease (RDD) is a proliferative histiocytic disorder of unknown etiology which is characterized by sinus histiocytosis with massive lymphadenopathy. In most cases, RDD has a benign course and treatment is not necessary. However, severe cases of RDD require treatment, and the treatment strategy is determined on the basis of the severity of the disease or the extranodal involvement of vital organs. We report a single case of RDD with atypical presentation of persistent constitutional symptoms, progressing pathologic fractures, and end-organ dysfunction, including acute kidney failure and liver cirrhosis with esophageal varices.